La autoevaluación en la Universidad EAFIT: Fundamentos y modelos (2004)
This article presents the self evaluation model followed by EAFIT University, for the process of institutional accreditation and as a permanent model for the redefinition of the strategic institutional objectives and the formulation of development plans. EAFIT University accepts self evaluation as the frequent balance and revision of its research, teaching, and social projection activities within the strategic frame, and defined by the institutional vision and mission, and through the confrontation with the current state of the social environment and the impact achieved in this last one.